A Small Molecule Antagonist of PD-1/PD-L1 Interactions Acts as an Immune Checkpoint Inhibitor for NSCLC and Melanoma Immunotherapy - Wang, Yuanyuan; Gu, Tingxuan; Tian, Xueli; Li, Wenwen; Zhao, Ran; Yang, Wenqian; Gao, Quanli; Li, Tiepeng; Shim, Jung-Hyun; Zhang, Chengjuan; Liu, Kangdong; Lee, Mee-Hyun (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors, such as monoclonal antibodies targeting programmed death 1 (PD-1) and programmed death ligand-1 (PD-L1), have achieved enormous success in the treatment of several cancers. However, monoclonal antibodies are expensive to produce, have poor tumor penetration, and may induce autoimmune side effects, all of which limit their application. Here, we demonstrate that PDI-1 (also name PD1/PD-L1 inhibitor 1), a small molecule antagonist of PD-1/PD-L1 interactions, shows potent anti-tumor activity in vitro and in vivo and acts by relieving PD-1/PD-L1-induced T cell exhaustion. We show that PDI-1 binds with high affinity to purified human and mouse PD-1 and PD-L1 proteins and is a competitive inhibitor of human PD-1/PD-L1 binding in vitro. Incubation of ex vivo activated human T cells with PDI-1 enhanced their cytotoxicity towards human lung cancer and melanoma cells, and concomitantly increased the production of granzyme B, perforin, and inflammatory cytokines. Luciferase reporter assays showed that PDI-1 directly increases TCR-mediated activation of NFAT in a PD-1/PD-L1-dependent manner. In two syngeneic mouse tumor models, the intraperitoneal administration of PDI-1 reduced the growth of tumors derived from human PD-L1-transfected mouse lung cancer and melanoma cells; increased and decreased the abundance of tumor-infiltrating CD8+ and FoxP3+ CD4+ T cells, respectively; decreased the abundance of PD-L1-expressing tumor cells, and increased the production of inflammatory cytokines. The anti-tumor effect of PDI-1 in vivo was comparable to that of the anti-PD-L1 antibody atezolizumab. These results suggest that the small molecule inhibitors of PD-1/PD-L1 may be effective as an alternative or complementary immune checkpoint inhibitor to monoclonal antibodies.